PENDAMPINGAN PROGRAM PEMBERDAYAAN MASYARAKAT MELALUI PELAYANAN SOSIAL DAN PENDIDIKAN DI MASJID AGUNG BANGIL - Siti Yumnah (As-Sidanah, 2021)
Community empowerment is one of the important activities that needs to be carried out to empower, especially mosque-based community empowerment. The community service method used is mosque-based management, which aims to find out mosque-based community empowerment for social and educational services at the Great Mosque of Bangil by conducting previous observations and collecting data and interviews with parties involved in community empowerment at the Great Mosque Bangil. And the results of the research got are that community empowerment at the Great Bangil Mosque can foster and educate the community and children through mosque committee programs developed through the social and educational fields.